El ganado comunal en la Mixteca Alta: de la época colonial al Siglo XX. El caso de Tepelmeme - Mendoza García, J. Edgar (El Colegio de México, A.C., 2002)
This is an analysis of the political  and economic factors than allowed the keeping of a herd of goats as communal property from the  república de indios of the colonial period until municipal administrations at the beginning of the twentieth century  in the region called the Mixteca Alta.The case of Tepelmeme, Oaxaca, is the basis of an account of the economic importance of communal property in the local governments of villages and  municipios, as well of the opposition of villages to liberal laws of the nineteenth century.In short, during the colonial period and part of the nineteenth century,  communal property was the main economic support of Indian villages. Not only was this property equivalent to communal  savings kept  for  critical  moments, but  also  an  economic means  that  allowed financing public  administration and  paying for religious services. Moreover, it was a factor that gave cohesion to these villages and inserted them into a regional economy.